Study on improved control strategy of virtual synchronous generator - Li, Ji; Yang, Fan; Wang, Huanmin; Chu, Bingqing (Frontiers in Smart Grids, 2024)
Virtual Synchronous Generator (VSG) control technology for photovoltaic, energy storage, wind power, and other new energy to provide flexibility in the grid interface characteristics, is conducive to improving the stability of the power system and has been widely considered by many scholars. In this work, an improved VSG control method is proposed to realize the complete decoupling of the frequency response time constant and inertia of the active power control loop and to reduce the complexity of VSG system parameter design. To avoid the frequent action of the VSG system caused by small-scale frequency change perturbation, this study proposes a VSG frequency optimization control method for VSG frequency control with rated angular velocity ωset feedforward composed of multivariate factors based on the consideration of primary frequency regulation dead zone. The impact of VSG parameter design on the system is investigated through the system response characteristics of power scheduling and primary frequency regulation at grid connection and the small-signal dynamic characterization of the improved VSG. The improved control method system has an active power overshoot of 7% and a maximum frequency deviation of 0.17Hz. The improved control method improves the frequency response time by 0.1s and reduces the oscillation amplitude by 0.15Hz. The response speed of the improved control method is greatly improved, while the oscillation amplitude is reduced to meet the requirements of grid regulation. The VSG simulation model and experimental platform are constructed, and the simulation and experimental analysis verify the feasibility of the improved VSG control method.